Penerapan Media Pembelajaran PASTA Guna Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik Pada Materi Statistika - Rahma Dini, Disya Futhi; Hadi, Muhamad Sofian; Sundi, Venni Herli; Sugiyanti, Sugiyanti (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This study aims to determine the effect of students' problem solving abilities through the application of PASTA to statistical material. Data collection was carried out using pre-test and post-test. In this research there are four indicators, namely understanding the problem, planning the problem, implementing the plan and checking again. The results of the research show that the application of PASTA learning media to statistics material is able to improve students' mathematical problem solving abilities, this can be seen from the increase in test results from cycle I of 54% to cycle II of 93% after the application of PASTA learning media and the average of each indicator Mathematical problem solving abilities have reached completion and the results of learning mathematical problem solving abilities in cycle II can be seen from the number of students who completed the cycle II test, namely 26 students out of 28 students in class VII.